Out with the Old: Munitions Disposal, Marine Environments, and the Canadian Military - Souchen, Alex (Scientia Canadensis, 2023)
This article examines the history of the Canadian military’s disposal policies and practices for surplus and/or obsolete munitions from the 1940s to the 1960s. During that time, the military dumped ammunition, explosives, chemical weapons, and other unneeded ordnance at sea. Such practices were common worldwide and originated from the immense surpluses of weaponry leftover at the end of the Second World War. This article shows that munitions dumping took place on both the Atlantic and Pacific coasts, in the Great Lakes, the St. Lawrence River, and other inland waters. It further demonstrates the importance of placing Canadian dumping policies and operations within their historical context, as wider political, logistical, scientific, environmental, and military factors influenced decision-making and implementation. Yet dumping was not without serious consequences for marine organisms, environments, and the communities that depend on the sea for their livelihoods. By taking a use-centred approach to military technologies and focusing on the disposal regimes for conventional and chemical munitions, this article shows that the afterlives of military technologies can embody the environmental legacies of war.